Association Analysis Between the Functional Single Nucleotide Variants in miR-146a, miR-196a-2, miR-499a, and miR-612 With Acute Lymphoblastic Leukemia - Jiménez-Morales, Silvia; Núñez-Enríquez, Juan Carlos; Cruz-Islas, Jazmín; Bekker-Méndez, Vilma Carolina; Jiménez-Hernández, Elva; Medina-Sanson, Aurora; Olarte-Carrillo, Irma; Martínez-Tovar, Adolfo; Flores-Lujano, Janet; Ramírez-Bello, Julian; Pérez-Saldívar, María Luisa; Martín-Trejo, Jorge Alfonso; et al. (Frontiers in Oncology, 2021)
Background. Acute lymphoblastic leukemia (ALL) is characterized by an abnormal proliferation of immature lymphocytes, in whose development involves both environmental and genetic factors. It is well known that single nucleotide polymorphisms (SNPs) in coding and non-coding genes contribute to the susceptibility to ALL. To determine whether SNPs in miR-146a, miR-196a-2, miR-499a, and miR-612 genes are associated with the risk to ALL in pediatric Mexican population. Methods: A multicenter case-control study was carried out including patients with de novo diagnosis of ALL and healthy subjects as control group. The DNA samples were obtained from saliva and peripheral blood and the genotyping of rs2910164, rs12803915, rs11614913 and rs3746444 was performed using the 5 'exonuclease technique. Gene-gene interaction was evaluated by the Multifactor dimensionality reduction (MDR) software. Results: miR-499a rs3746444 showed significant differences among cases and controls. The rs3746444G allele was found as risk factor to ALL (OR 1.6, 95% CI 1.05-2.5, P = 0.028). The homozygous GG genotype of rs3746444 confers higher risk to ALL than the AA genotype (OR 5.3, 95% CI 1.23-23.4, p = 0.01). Moreover, GG genotype highly increases the risk to ALL in male group (OR 17.6, CI 95% 1.04-298.9, p=0.00393). In addition, an association in a gender-dependent manner among SNPs located in miR-146a, and miR-196a-2 genes and ALL susceptibility was found. Conclusion: Our findings suggest that SNP located in miR-499a, miR-146a, and miR-196a-2 genes confer risk to ALL in Mexican children. Experimental analysis to decipher the role of these SNPs in human hematopoyesis could improve our understanding of the molecular mechanism underlying the development of ALL.